HUBUNGAN ANTARA MORAL DISENGAGEMENT DENGANACADEMIC DISHONESTY PADA MAHASISWA ILMU SOSIALDAN HUMANIORA (SOSHUM) - Amara Verucha; Rahayu Hardianti Utami (Jurnal Riset Psikologi, 2025)
The emphasis on grades as a benchmark for success in education has led some individuals to overlook other important aspects, resulting in dishonest behaviors such as academic dishonesty. Most studies indicate that students in the social sciences and humanities are among the main contributors to this behavior. However, both society and individuals themselves often display permissive responses, which can encourage the emergence of moral disengagement. In this context, the researcher aimed to examine the relationship between moral disengagement and academic dishonesty among social sciences and humanities students, as well as to provide an overview of each variable and its dimensions. This study employed a quantitative approach involving 457 social sciences and humanities students in Indonesia and was analyzed using Spearman’s correlation test. The results showed that the majority of participants fell into the moderate category for both moral disengagement (75.7%) and academic dishonesty (69.8%). Additionally, a positive and significant relationship was found between moral disengagement and overall academic dishonesty (rₛ = 0.464; p < 0.01), as well as with its three dimensions, plagiarism (rₛ = 0.450), unauthorized collaboration (rₛ = 0.429), and cheating (rₛ = 0.396).